The Urgency of Reformulating the Handling of Petty Corruption through a Peaceful Fine Scheme in Indonesia: Urgensi Reformulasi Penanganan Korupsi Ringan Melalui Skema Denda Damai di Indonesia - Marlina, Andi; Karauwan, Donny Eddy Sam; Juanedy, Achmad; Ramadhani, Anugrah (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
Petty corruption is a form of corruption with relatively small state losses, but still contributes to the formation of a systemic culture of corruption. Law enforcement in Indonesia against this type of crime has tended to employ a uniform retributive approach, without considering the value of the loss and the severity of the offense. As a result, there are inequalities in court decisions and inefficiencies in case handling costs. This research employs a normative juridical method, combining a conceptual and case-based approach, to examine the handling of petty corruption from the perspective of substantive justice and the urgency of implementing an amicable fine mechanism (schikking). The results show that the amicable fine mechanism can be an effective and fair solution in handling petty corruption cases. In addition to encouraging the return of state losses quickly and efficiently, this approach is also in accordance with the principle of restorative justice which prioritizes recovery over retribution. For this reason, legal reconstruction is needed, which includes revising Article 4 of the Anti-Corruption Law and strengthening the legality of schikking, so that it can be formally applied to petty corruption cases in Indonesia.